The relevance of management research debate: a historical view, 1876–2018. Issue 3 (25th February 2022) - Wood, Thomaz; Souza, Renato; Caldas, Miguel P.
Abstract : Purpose: This paper aims to map how the debate concerning the relevance of management research historically evolved to (a) determine if B-schools and management researchers have been uninterested bystanders, as critics posit, or if they have had a relevant role, and (b) discover if a pathway for management research becoming socially relevant has been established by such debate. Design/methodology/approach: This study performed a citation network analysis of the scientific literature concerning the relevance of management research. The network had a total of 1, 186 research papers published between 1876 and 2018. Findings: The results show that from a minimal to peripheral role at the beginning and middle stages, management researchers have rather taken over this debate since the 1990s; the key components of the citation network reveal a strong convergence on what needs to be done, but no convergence on how to do it; and the debate has failed to generate actual change. Originality/value: This study maps the debate concerning the relevance of management research since its historical inception using a method underused in management history research. It reveals the main path of the debate and the journals that echoed such debate.